Optimization ofS/Fe ratio for enhanced nitrobenzene biological removal in anaerobicSystem amended withSulfide-modified nanoscale zerovalent iron. (May 2020) - Zhang, Dejin; Li, Yang; Sun, Aiwu; Tong, Siqi; Jiang, Xinbai; Mu, Yang; Li, Jiansheng; Han, Weiqing; Sun, Xiuyun; Wang, Lianjun; Shen, Jinyou
Abstract: Anaerobic reduction of nitrobenzene (NB) can be efficiently enhanced bySupplementing withSulfide-modified nanoscale zerovalent iron (S-nZVI). In thisStudy, S/Fe ratio ofS-nZVI was further optimized for enhancing biological NB removal in anaerobicSystem amended withS-nZVI and inoculated by anaerobicSludge. The results indicated that the performance andStability of the coupled anaerobicSystem for NB reduction and aniline formation were remarkably improved byS-nZVI atS/Fe molar ratio of 0.3 (0.3S-nZVI). TheSecretion of extracellular polymericSubstances (EPS), transformation of volatile fatty acids (VFAs), yield of methane and activity ofSeveral key enzymes could be efficiently improved by 0.3S-nZVI. Furthermore, Species related to NB reduction, fermentation, electroactivity and methanogenesis could be enriched in 0.3S-nZVI coupled anaerobicSystem, with remarkable improvement in the biodiversity observed. ThisStudy demonstrated thatSulfidation would be a promising method to improve the performance of nZVI in coupled anaerobicSystems for the removal of recalcitrant nitroaromatic compounds from wastewater. Graphical abstract: Image 1 Highlights: NB reduction andSubstrate turnover was improved byS-nZVI in anaerobicSystem. ecretion of extracellular polymericSubstances was enhanced byS-nZVI. AppropriateSulfidation could improveSystemStability of the long-term operation. Certain core functional genera were enriched in the coupledSystem. Key enzymatic activities wereStimulated by nZVI with appropriateSulfidation.